Pengaruh Kepemimpinan,Kompensasi,Dan Lingkungan Kerja Fisik Terhadap Kepuasan Kerja Karyawan Pada Pt. Putra Bhineka Perkasa Denpasar - sujana, kadek; dewi, A.A.sg kartika (E-Jurnal Manajemen, 2013)
800x600 Job satisfaction as a matter that relates to the work carried out and the response of the attitude of the employees themselves . This study has the main objective to find whether there was simultaneous partial and significant effect , and the dominant influence of the variables of leadership , compensation , and the physical work environment on job satisfaction of employees at PT . Bhineka Putra Perkasa . Inferred F count ( 80.579) exceeds the value of F table ( 2,70). Variable leadership , compensation , and physical work environment is partially positive and significant effect on job satisfaction of employees at PT . Bhineka Putra Perkasa , where the t value ( 6.957) for the leadership variable , t value ( 2.686) for variable compensation and t value ( 2,334) variable work environment , exceeding the value of t table ( 1.671). Keywords : job satisfaction , leadership , compensation , physical work environment . Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif"; mso-bidi-font-family:"Times New Roman";}